Plant beneficial microbiome a boon for improving multiple stress tolerance in plants - Ali, Sajad; Tyagi, Anshika; Mir, Rakeeb Ahmad; Rather, Irfan A.; Anwar, Yasir; Mahmoudi, Henda (Frontiers in Plant Science, 2023)
Beneficial microbes or their products have been major drivers for improving adaptive and growth features in plants under biotic and abiotic stress conditions. However, the majority of these studies so far have been utilized against individual stressors. In comparison to individual stressors, the combination of many environmental stresses that plants experience has a greater detrimental effect on them and poses a threat to their existence. Therefore, there is a need to explore the beneficial microbiota against combined stressors or multiple stressors, as this will offer new possibilities for improving plant growth and multiple adaptive traits. However, recognition of the multifaceted core beneficial microbiota from plant microbiome under stress combinations will require a thorough understanding of the functional and mechanistic facets of plant microbiome interactions under different environmental conditions in addition to agronomical management practices. Also, the development of tailored beneficial multiple stress tolerant microbiota in sustainable agriculture necessitates new model systems and prioritizes agricultural microbiome research. In this review, we provided an update on the effect of combined stressors on plants and their microbiome structure. Next, we discussed the role of beneficial microbes in plant growth promotion and stress adaptation. We also discussed how plant-beneficial microbes can be utilized for mitigating multiple stress in plants. Finally, we have highlighted some key points that warrant future investigation for exploring plant microbiome interactions under multiple stressors.